Integrated pest management for shoot ï¬‚y in sorghum during post rainy season in Maharashtra - Subbarayudu, B; Bhagwat, V R; Shyamprasad, G; Kalisekar, A; Babu, K S; Swarna, R (Indian Journal of Plant Protection, 2020)
Short Communication